Intellectual capital reporting at universities – the Austrian approach. (15th November 2006) - Renzl, Birgit
European higher education is in a state of transition. Universities are facing an increasingly competitive environment. Intellectual capital serves as a key resource for those organisations. The paper deals with intellectual capital reporting in the university context, presenting the Austrian approach. Austrian universities are required by law to report intellectual capital beginning in 2005. The paper illustrates the case of intellectual capital reporting at the Department of Management of the University of Innsbruck/Austria, which provides a three-year pilot of intellectual capital reporting in the higher education context.